Analisis Faktor Pada Ibu Hamil Trimester III Terhadap Persepsi Dan Pengaruh Tidak Melakukan Hubungan Seksual - Timisela, Joula; Nurhaedah, Nurhaedah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Pregnancy is a transitional period that affects a woman's physical, psychological, and social aspects, including sexual activity. In the third trimester, many pregnant women choose not to have sexual intercourse due to various perceptions and concerns. The purpose of this study was to analyze the factors that influence the perception of pregnant women in the third trimester towards the decision not to have sexual intercourse, as well as its impact on the physical and psychological condition of pregnant women. This study used a descriptive analytical approach with a quantitative method. The sample consisted of 60 pregnant women in the third trimester at Health Center X, who were selected using a purposive sampling technique. The results showed that the main influencing factors were fear of harming the fetus (80%), physical and emotional changes (65%), lack of knowledge about sexual intercourse during pregnancy (60%), and cultural influences and myths (55%). In addition, not having sexual intercourse also has an impact on increased anxiety, tension in husband and wife relationships, and decreased emotional satisfaction. Education and counseling are needed for pregnant women and their partners regarding safe sexual activity during pregnancy.